Association Between Exercise Self-Efficacy and Health-Related Quality of Life Among Dialysis Patients: A Cross-Sectional Study - Zhang, Fan; Liao, Jing; Zhang, Weihong; Huang, Liuyan (Frontiers in Psychology, 2022)
Background: Exercise self-efficacy is a vital determinant of an individual's active participation in regular exercise, and exercise is a critical component of improving health-related quality of life (HRQOL) in dialysis patients. This study aimed to describe the relationship between exercise self-efficacy and HRQOL in dialysis patients. Methods: A cross-sectional study was conducted in Shanghai, China. Structured questionnaires applied to the patients collected socio-demographic and disease-related information. Physical activity was assessed by a self-administered questionnaire, and the Exercise Self-Efficacy Scale (ESES) was used to measure exercise self-efficacy. Health-related quality of life was evaluated by the Kidney Disease Quality of Life Instrument-Short Form version 1.3 (KDQOL-SFTM v1.3). Data were analyzed using a univariate generalized linear model, Spearman correlation, and hierarchical multiple regression. Results: A positive association was observed between exercise self-efficacy and HRQOL (r=0.310, P<0.001). Physical activity as a predictor variable explained 9.8% of the variance in overall HRQOL (P<0.001). Exercise self-efficacy explained an additional 7.1% of the HRQOL variance. In total, 24.6% of the variation in the HRQOL is explained by the socio-demographic variables, disease-related factors, physical activity, and exercise self-efficacy. Conclusion: Overall, only 16.9% of the change in HRQOL was explained by physical activity and exercise self-efficacy. Future research is still needed to explore further the factors influencing the HRQOL in dialysis patients. However, this finding suggests the need to consider the importance of HRQOL and physical activity as well as exercise self-efficacy when developing intervention programs.